Detection and Removal of Lead from the Local Industrial Wastewaters - Jabeen, Gugan; Khurshid, Shazia (Asian Journal of Chemistry, 2012)
This work reported the removal of lead from the samples of effluents collected from a local industrial cluster by its adsorption on Nymphaea alba (nilofar flower). The estimation of lead in industrial effluents before and after adsorption was accomplished applying atomic absorption spectrometry.